Advokasi Aliansi Masyarakat Sipil: Kegagalan Merebut Aksesibilitas Pengelolaan Corporate Social Responsibility Melalui Peraturan Daerah - Ahmad Shodikin; Susetiawan Susetiawan (Journal of Social Development Studies, 2020)
Alliance of Civil Society Organization (ACSO) Bojonegoro is striving to solve the problem by advocating the CSR issue which have more fair and sustainable through public policy (local regulation) about CSR. The main research question is how the advocacy by ACSO in obtaining the access of CSR management using the local regulation? This research uses qualitative approach and utilize various primary data from interviews and observations, also secondary data from news and documentation. This article shows that the CSR advocacy through local regulation in Bojonegoro district was not successful. The relation between ACSO and DPRD was not harmonious. The DPRD chose to ratify the draft of CSR management that has been formulated by the DPRD members. The political parties inside DPRD were stronger to force and formulate public policy of CSR.